Sejarah Peninggalan Rumah Adat Bolon di Desa Pematang Purba, Kabupaten Simalungun - Saragih, Hakimi Arsya; Lubis, Fauziah; Jamil, Khairul (Mahesa Research Center (PT. Mahesa Global Publishing), 2020)
This article discusses the architectural history of Rumah Bolon in Pematang Purba Village, Simalungun Regency. Rumah Bolon is a typical Batak traditional house which is usually the residence of the king and his entire extended family. This research uses qualitative research methods, with a historical approach. In the historical approach, there are four writing steps, namely: heuristics, verification or criticism, interpretation, and historiography. Bolon's house is a symbol of the greatness and beauty of Simalungun's distinctive architecture. In its construction, it must go through various kinds of long and strict ceremonies. Not all wood can also be used as raw material for dast in its manufacture. In the Rumah Bolon architecture, the design from top to bottom, has been arranged in great detail. In addition, in the Rumah Bolon building there are also Simalungun colors; red; white; and black. There are also several carvings in Rumah Bolon that symbolize the meanings of greatness, mutual cooperation, and togetherness.